Negative electrode sheet, secondary battery, method for manufacturing secondary battery, and electric device

CN122889700APending Publication Date: 2026-10-09CHERY AUTOMOBILE CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611373215.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-04
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

现有改善低温性能的单一方案分为两类:一类仅调整电解液溶剂配比,虽降低凝固点,但无法改善石墨嵌锂通道,低温快充依然析锂;另一类仅对石墨进行简单包覆改性,未搭配低温电解液体系,低温下SEI膜脆性开裂,每次充放电反复重构消耗锂源,循环寿命提升幅度不足10%

Benefits of technology

本申请提供的负极片,负极集流体表面的活性材料层采用“中间区域等厚,两侧的边缘区域的厚度梯度递减”的设计,具有上述结构的负极片可以持续补给边缘电解液,1000次深度循环后负极侧边无发白析锂粉末、无枝晶生成;对比传统等厚涂布电芯,完全消除边缘析锂失效模式,电芯安全等级显著提升,针刺、1C过充无冒烟、起火、热失控现象。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122889700A_ABST
    Figure CN122889700A_ABST
Patent Text Reader

Abstract

The application discloses a negative plate, a secondary battery, a preparation method of the secondary battery and an electric device. The negative plate comprises a negative current collector and an active material layer arranged on at least one surface of the negative current collector. The active material layer comprises a middle region and edge regions located on both sides of the middle region along a width direction. The thickness of the middle region is uniform and equal, and the thickness of the edge regions gradually decreases from the middle region to both side edges of the negative current collector. The active material layer on the surface of the negative plate provided above adopts the design of "uniform thickness of the middle region and gradually decreasing thickness of the edge regions on both sides", and the negative plate with the above structure can continuously supply edge electrolyte. After 1000 deep cycles, there is no white lithium powder and dendrite generation on the negative side edge. Compared with a traditional equal-thickness coating battery, the edge lithium precipitation failure mode is completely eliminated, the safety level of the battery is significantly improved, and there is no smoking, fire and thermal runaway phenomenon in the needle test and 1C overcharge test.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of battery technology, and more specifically, to a negative electrode, a secondary battery, a method for preparing the secondary battery, and an electrical device. Background Technology

[0002] Lithium-ion batteries store and release electrical energy by repeatedly inserting and deintercalating lithium ions between the positive and negative electrodes. With advantages such as high energy density, no memory effect, and low self-discharge, they have comprehensively replaced lead-acid and nickel-metal hydride batteries, becoming the core carrier for new energy transportation and electrochemical energy storage. As new energy vehicles expand into colder northern regions and outdoor energy storage power stations are widely deployed, the industry has imposed stringent requirements on the low-temperature discharge performance, long-term cycle stability, and safety and reliability of power batteries. Traditional lithium-ion battery technologies have revealed multiple unavoidable core defects.

[0003] However, traditional coating equipment uses a uniform slit die, resulting in a completely consistent coating thickness on the copper foil surface. (See [link]). Figure 1 During the drying process, a thick edge structure of coating buildup forms on the sides. At this thick edge, the graphite active material has a higher compaction degree than at the center of the electrode, resulting in lower porosity and less electrolyte storage. During battery charging and discharging, repeated lithium-ion insertion and extraction cause microscopic volume expansion and contraction of the electrode. The edge pores are compacted first, leading to rapid electrolyte consumption and inability to replenish in time, creating an electrolyte break-bridge effect. In the break-bridge area, lithium ions cannot properly insert into the graphite layer and can only deposit as metallic lithium on the electrode sides, continuously growing lithium dendrites. Lithium dendrites pose two major hazards: First, they consume the limited active lithium source within the cell, causing a rapid drop in battery capacity per hundred cycles; second, sharp lithium dendrites easily pierce the separator, causing micro-short circuits and self-discharge problems within the cell. Continued growth of lithium dendrites can ultimately lead to thermal runaway, fire, and explosion risks. Current industry-standard improvement methods are limited to controlling excessive thinning of the gasket and thickening of the separator. Excessive thinning leads to poor thickness consistency in the MD direction of the electrode, increases the distance between the positive and negative electrodes, and affects lithium-ion insertion and extraction. Thickening the separator directly reduces the energy density of the cell. Neither of these methods can eliminate the thick edge structure from the coating source, and they are only treating the symptoms, not the root cause.

[0004] Conventional carbonate electrolytes are mainly composed of ethylene carbonate and dimethyl carbonate, with an excessively high proportion of high-viscosity EC. When the ambient temperature drops below -10°C, the electrolyte viscosity index increases exponentially, significantly reducing the lithium-ion migration rate. Simultaneously, the original interlayer spacing of commercially available natural / artificial graphite is only about 0.335 nm, leading to a sharp increase in lithium-ion intercalation kinetics at low temperatures. During charging, a large amount of lithium cannot intercalate into the graphite and instead deposits directly on the negative electrode surface, resulting in lithium deposition at low temperatures far exceeding that at room temperature. Existing single-solution solutions for improving low-temperature performance fall into two categories: one only adjusts the electrolyte solvent ratio, which lowers the freezing point but fails to improve the graphite lithium intercalation channels, resulting in lithium deposition even during low-temperature fast charging; the other only performs simple coating modifications on the graphite without a low-temperature electrolyte system, leading to brittle cracking of the SEI film at low temperatures. Repeated reconstruction during each charge-discharge cycle consumes the lithium source, resulting in a cycle life improvement of less than 10%.

[0005] Currently, the industry's battery improvement solutions adopt a single-point optimization approach, such as only improving the electrode sheet, electrolyte, negative electrode material, and formation process. There is no integrated technical solution that can simultaneously solve the four types of coupled defects: electrolyte depletion at thick edges, high resistance to low-temperature lithium intercalation in graphite, easy damage to the low-temperature SEI film, and uneven film formation at the edges during the formation stage. Single improvements offer limited performance enhancements, and most improvement processes require additional specialized equipment, significantly increasing mass production costs and making large-scale industrial promotion difficult. Summary of the Invention

[0006] The purpose of this application is to overcome the problems existing in the prior art and provide a negative electrode sheet, a secondary battery, a method for preparing a secondary battery, and an electrical device for using it.

[0007] The technical problem solved by this application is achieved by the following technical solution.

[0008] This application provides a negative electrode sheet, comprising: A negative electrode current collector; and an active material layer disposed on at least one surface of the negative electrode current collector; The active material layer includes a central region and edge regions located on both sides of the central region along the width direction; The thickness of the middle region is uniform, and the thickness of the edge region decreases continuously from the middle region to the two sides of the negative electrode current collector, with a thickness range H of 3μm-35μm. The active material layer includes a negative electrode active material, a conductive agent, a binder, and a ceramic filler, and the negative electrode active material includes graphite; The graphite includes expanded-layer artificial graphite and natural graphite, wherein: the expanded-layer artificial graphite has a mass percentage content of 50%-90% in the active material layer, and the natural graphite has a mass percentage content of 5%-20% in the active material layer; wherein: the expanded-layer artificial graphite is obtained by expanding and modifying artificial graphite under an inert atmosphere at 800℃-1200℃, and the graphite crystal interlayer spacing of the expanded-layer artificial graphite is 0.336nm-0.342nm.

[0009] In some embodiments of this application, the width of the middle region is 30mm-800mm, and the edge regions located on both sides of the middle region are symmetrically arranged, with the width W of the edge region on one side being 0.5mm-20.0mm.

[0010] In some embodiments of this application, the thickness of the intermediate region is 100μm-120μm.

[0011] In some embodiments of this application, the surface of the negative electrode current collector is provided with at least one layer of the active material. When the active material layer has two or more layers, the type and particle size of the graphite in the different active material layers are different.

[0012] In some embodiments of this application, the binder includes at least one of sodium carboxymethyl cellulose, polyacrylic acid, polyvinyl alcohol, polyamide-imide, polyacrylate, polyacrylate, polyimide, and nitrile rubber; the conductive agent includes at least one of carbon nanotubes, conductive carbon black, discrete carbon nanotubes, conductive graphite, and graphene; and the ceramic filler includes at least one of nano-alumina, boehmite, and zirconium oxide.

[0013] In some embodiments of this application, the active material layer comprises, by mass percentage: 50%-90% expanded artificial graphite, 5%-20% natural graphite, 0.3%-2% carbon nanotubes, 0.6%-1.5% carboxymethyl cellulose, 0.5%-1.5% polyacrylic acid, 0.8%-2% styrene-butadiene rubber latex, and 0.5%-1.2% nano-alumina; wherein the nano-alumina has a particle size of 20nm-90nm.

[0014] This application also provides a secondary battery, which includes a positive electrode, a negative electrode, a separator, an electrolyte, and a packaging shell, wherein the negative electrode is the aforementioned negative electrode.

[0015] In some embodiments of this application, the electrolyte comprises a solute, a composite organic solvent, and a composite low-temperature functional additive, wherein: The solute in the electrolyte includes at least one of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, LiDFOB, and LiBOB, and the concentration of the solute in the electrolyte is 1.0 mol / L to 1.3 mol / L. The composite organic solvent includes ethylene carbonate, dimethyl carbonate, and low-viscosity low-temperature ester solvents. The low-viscosity low-temperature ester solvents include at least one of ethyl propionate, methyl acetate, ethyl acetate, methyl propionate, methyl butyrate, and propyl acetate. The overall freezing point of the composite organic solvent is ≤-65℃. The composite low-temperature functional additive includes 2%-3% fluoroethylene carbonate and 0.5%-2% ethylene sulfate, which constitute 2%-3% of the total volume of the electrolyte.

[0016] In some embodiments of this application, the separator comprises one or more of polyethylene and polypropylene coated with single-sided nano-ceramic coating, and the ceramic coating surface of the separator is arranged facing the negative electrode sheet.

[0017] This application also provides a method for preparing the above-mentioned secondary battery, comprising the following steps: coating the active material layer on the negative electrode current collector, followed by drying and rolling, assembly, liquid injection, formation, and capacity testing to obtain the secondary battery.

[0018] In some embodiments of this application, the method of coating the active material layer on the negative electrode current collector includes: using a segmented adjustable stepped coating die to coat the active material layer on the negative electrode current collector, wherein the coating thickness in the middle region is 100μm-120μm, and the coating thickness decreases linearly from the middle region to the edge regions on both sides, with the thickness difference controlled between 3μm-35μm.

[0019] In some embodiments of this application, drying and rolling include: after coating the active material layer on the negative electrode current collector, thoroughly drying it in a preheating section of 125℃-135℃-130℃, a constant-speed drying section of 130℃-105℃-95℃, and a decreasing-speed drying section of 120℃-135℃-110℃; after drying, rolling the negative electrode sheet to control the compaction density at 1.45g / cm³-1.65g / cm³.

[0020] In some embodiments of this application, assembly and electrolyte injection include: assembling and packaging the positive electrode, separator, and negative electrode using a winding or stacking process according to product requirements; injecting a quantitative amount of electrolyte into the cell and then vacuum sealing it; and allowing it to stand at room temperature for 48 hours to allow the electrolyte to fully wet the electrode.

[0021] In some embodiments of this application, formation and capacity testing include low-temperature pre-formation, conventional formation, and capacity testing aging. The low-temperature pre-formation includes controlling the ambient temperature to 5°C-10°C and charging with a step-by-step constant current of 0.01C-0.03C to the cutoff voltage of 3.2V.

[0022] In some embodiments of this application, the secondary battery includes any one of nickel-cobalt-manganese, lithium manganese oxide, lithium iron phosphate, and lithium manganese iron phosphate system lithium-ion batteries.

[0023] This application also provides an electrical device, which includes the aforementioned secondary battery.

[0024] This application has the following beneficial effects: The negative electrode sheet provided in this application adopts a design of "equal thickness in the middle region and decreasing thickness gradient in the edge regions on both sides" for the active material layer on the surface of the negative electrode current collector. The negative electrode sheet with the above structure can continuously replenish the edge electrolyte. After 1000 deep cycles, there is no white lithium powder or dendrite formation on the side of the negative electrode. Compared with the traditional uniform thickness coating cell, the edge lithium plating failure mode is completely eliminated, the cell safety level is significantly improved, and there is no smoke, fire or thermal runaway phenomenon during needle penetration and 1C overcharge. Attached Figure Description

[0025] To more clearly illustrate the technical solutions of the embodiments of this application, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of this application and should not be regarded as a limitation of the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.

[0026] Figure 1 A schematic diagram of the cross-section of a traditional uniform thickness coated negative electrode sheet; Figure 2 A schematic diagram of the cross-sectional structure of the stepped optimized negative electrode provided in this application; Figure 3 A schematic diagram of the cross-sectional view of the upper lip of the negative electrode stepped coating die provided in this application; Figure 4 A schematic cross-sectional view of the lower lip of the negative electrode stepped coating die provided in this application; Reference numerals: H represents the thickness range of the edge region, and W represents the width of the edge region on one side. Detailed Implementation

[0027] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions in the embodiments of this application will be clearly and completely described below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased commercially.

[0028] The following is a detailed description of a negative electrode sheet, a secondary battery, a method for preparing the secondary battery, and an electrical device provided in the embodiments of this application.

[0029] In a first aspect, this application provides a negative electrode sheet, comprising: A negative electrode current collector; and an active material layer disposed on at least one surface of the negative electrode current collector; The active material layer includes a central region and edge regions located on both sides of the central region along the width direction; The thickness of the middle region is uniform, and the thickness of the edge region decreases continuously from the middle region to the two sides of the negative electrode current collector, with a thickness range H of 3μm-35μm. The active material layer includes a negative electrode active material, a conductive agent, a binder, and a ceramic filler, and the negative electrode active material includes graphite; The graphite includes expanded-layer artificial graphite and natural graphite, wherein: the expanded-layer artificial graphite has a mass percentage content of 50%-90% in the active material layer, and the natural graphite has a mass percentage content of 5%-20% in the active material layer; wherein: the expanded-layer artificial graphite is obtained by expanding and modifying artificial graphite under an inert atmosphere at 800℃-1200℃, and the graphite crystal interlayer spacing of the expanded-layer artificial graphite is 0.336nm-0.342nm.

[0030] See Figure 2 The negative electrode sheet provided in this application abandons the industry-standard uniform thickness design of the active material layer on the surface of the negative electrode current collector. Instead, it adopts a design of "uniform thickness in the middle region and a gradient decrease in thickness in the edge regions on both sides." The central region retains a complete thick coating to ensure capacity, while the thickness of the edge regions on both sides decreases linearly to suppress edge lithium deposition. The negative electrode sheet provided above, through the optimized coating design in the edge regions, can store free electrolyte. During the cycling process, electrolyte is continuously replenished to the inner coating edge, completely solving the problem of rapid drying and bridge breakage of the edge electrolyte. At the same time, the gradient thinning structure in the edge regions can eliminate the accumulation of thick coating on the side edges, reduce edge compaction stress, and make the lithium ion deposition environment more consistent with the center of the electrode sheet, thus suppressing edge lithium deposition from the root of the physical structure.

[0031] Multiple experiments have confirmed that if the thickness difference H in the edge region is less than 3 μm, the prepared negative electrode sheet is close to uniform thickness coating, the electrolyte is consumed quickly, and the cycle life is affected. If the thickness difference H in the edge region is greater than 35 μm, the height difference along the thickness is too large, which affects the lithium ion insertion and extraction and makes it easy for lithium to be deposited and white spots to appear.

[0032] The expanded-layer artificial graphite described in this application is obtained by expanding and modifying artificial graphite under an inert atmosphere at 800℃-1200℃. The interlayer spacing of the graphite crystals in the expanded-layer artificial graphite is 0.336nm-0.342nm. In this application, the negative electrode active material in the negative electrode active material layer is screened and modified. For example, artificial graphite is subjected to high-temperature heat treatment under an inert atmosphere to appropriately expand the interlayer spacing to 0.336nm-0.342nm, widening the lithium-ion insertion and extraction channels and significantly reducing charge transfer resistance at low temperatures. 20-80nm nano-alumina is then uniformly filled between the graphite particles to form an elastic three-dimensional buffer network, buffering the graphite volume deformation during charging and discharging, while simultaneously adsorbing and storing electrolyte, further improving the edge ion conduction environment. Compared to ordinary graphite: unexpanded graphite has an interlayer spacing of 0.335nm, and the lithium insertion resistance at -20℃ increases by more than 40%, making lithium deposition extremely easy; the modified graphite in this application shows significantly improved low-temperature kinetic performance.

[0033] In some alternative embodiments, the width of the intermediate region is 30mm-800mm, and the edge regions located on both sides of the intermediate region are symmetrically arranged, with the width W of the edge region on one side being 0.5mm-20.0mm.

[0034] In some alternative embodiments, the thickness of the intermediate region is 100μm-120μm.

[0035] In some embodiments of this application, the surface of the negative electrode current collector is provided with at least one layer of the active material. When the active material layer has two or more layers, the types and particle sizes of the graphite in the different active material layers are different, which facilitates rapid wetting by the electrolyte.

[0036] In some alternative embodiments, the binder includes at least one of sodium carboxymethyl cellulose, polyacrylic acid, polyvinyl alcohol, polyamide-imide, polyacrylate, polyacrylate, polyimide, and nitrile rubber; the conductive agent includes at least one of carbon nanotubes, conductive carbon black, discrete carbon nanotubes, conductive graphite, and graphene; and the ceramic filler includes at least one of nano-alumina, boehmite, and zirconium oxide.

[0037] In some optional embodiments, the active material layer comprises, by weight percentage: 50%-90% expanded artificial graphite, 5%-20% natural graphite, 0.3%-2% carbon nanotubes, 0.6%-1.5% carboxymethyl cellulose, 0.5%-1.5% polyacrylic acid, 0.8%-2% styrene-butadiene rubber latex, and 0.5%-1.2% nano-alumina; wherein the nano-alumina has a particle size of 20nm-90nm.

[0038] Secondly, this application provides a secondary battery, which includes a positive electrode, a negative electrode, a separator, an electrolyte, and a packaging shell, wherein the negative electrode is the aforementioned negative electrode.

[0039] In some optional embodiments, the electrolyte comprises a solute, a complex organic solvent, and a complex low-temperature functional additive, wherein: The solute in the electrolyte includes at least one of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, LiDFOB, and LiBOB, and the concentration of the solute in the electrolyte is 1.0 mol / L to 1.3 mol / L. The composite organic solvent includes ethylene carbonate, dimethyl carbonate, and low-viscosity low-temperature ester solvents. The low-viscosity low-temperature ester solvents include at least one of ethyl propionate, methyl acetate, ethyl acetate, methyl propionate, methyl butyrate, and propyl acetate. The overall freezing point of the composite organic solvent is ≤-65℃. The composite low-temperature functional additive includes 2%-3% fluoroethylene carbonate and 0.5%-2% ethylene sulfate, accounting for 0.5%-2% of the total volume of the electrolyte. By introducing low-viscosity, low-temperature ester solvents such as ethyl propionate and ethyl acetate into the solvent system, the overall freezing point of the electrolyte is lowered to below -65°C, resulting in good electrolyte fluidity in low-temperature environments. Combined with the FEC (fluoroethylene carbonate) + VEC (ethylene sulfate) composite low-temperature functional additive, a fluorinated flexible SEI film is generated on the graphite surface during the low-temperature charging process. Traditional SEI films generated by a single FEC additive exhibit high low-temperature brittleness, leading to repeated cracking and reconstruction during charge-discharge cycles, resulting in lithium source loss. The SEI film prepared by the synergistic use of the two additives in this application is resistant to low temperatures, has strong ductility, remains intact during cycling, and continuously protects the graphite anode.

[0040] In some alternative embodiments, the separator comprises one or more of polyethylene and polypropylene coated with a single-sided nano-ceramic coating, with the ceramic-coated side of the separator facing the negative electrode. The ceramic coating can store electrolyte, enhance the insulation protection of the electrode edges, and prevent lithium dendrites from piercing the separator and causing micro-short circuits.

[0041] Thirdly, this application provides a method for preparing the above-mentioned secondary battery, comprising the following steps: coating the active material layer on the negative electrode current collector, followed by drying and rolling, assembly, liquid injection, formation, and capacity testing to obtain the secondary battery.

[0042] In some optional embodiments, the method of coating the active material layer on the negative electrode current collector includes: using a segmented adjustable stepped coating die to coat the active material layer on the negative electrode current collector, wherein the coating thickness in the middle region is 100μm-120μm, and the coating thickness decreases linearly from the middle region to the edge regions on both sides, with the thickness difference controlled between 3μm-35μm.

[0043] In some optional embodiments, drying and rolling include: after coating the active material layer on the negative electrode current collector, thoroughly drying it in a preheating section of 125℃-135℃-130℃, a constant-speed drying section of 130℃-105℃-95℃, and a decreasing-speed drying section of 120℃-135℃-110℃; after drying, rolling the negative electrode sheet to control the compaction density at 1.45g / cm³-1.65g / cm³.

[0044] In some optional embodiments, assembly and electrolyte injection include: assembling and packaging the positive electrode, separator, and negative electrode using a winding or stacking process according to product requirements; injecting a quantitative amount of electrolyte into the cell and then vacuum sealing it; and allowing it to stand at room temperature for 36-48 hours to allow the electrolyte to fully wet the electrode.

[0045] In some optional embodiments, formation and capacity testing include low-temperature pre-formation, conventional formation, and capacity testing aging. Low-temperature pre-formation includes controlling the ambient temperature at 5°C-10°C and using a stepped constant current charging method with an extremely small current of 0.01C-0.03C to a cutoff voltage of 3.2V. Conventional formation involves charging at room temperature and high current throughout the process. The active material at the center of the electrode forms an SEI film first, while insufficient electrolyte and delayed reaction at the edges result in uneven SEI film thickness and excessively high local impedance, inducing lithium plating. This application adds a low-temperature (5-10°C) pre-formation step with an extremely small current below 0.03C before formal formation. At low temperatures, the lithium-ion migration rate is slow, allowing a uniform and dense SEI passivation layer to form slowly and synchronously at the center and edges of the electrode, eliminating interface differences between different areas of the electrode and preventing localized lithium plating from the early stages of cell activation.

[0046] In some alternative embodiments, the method for preparing the secondary battery is applicable to lithium-ion batteries based on nickel-cobalt-manganese, lithium manganese oxide, lithium iron phosphate, and lithium manganese iron phosphate systems.

[0047] In some alternative embodiments, the positive electrode active material layer in the positive electrode sheet may be disposed on one or both surfaces of the positive electrode current collector.

[0048] Those skilled in the art can choose a suitable method to prepare the positive electrode sheet. For example, it may include the following steps: mixing positive active material, binder and conductive agent to form a slurry, and then coating it onto the positive current collector.

[0049] The specific type of positive electrode active material is not particularly limited, as long as it can satisfy the requirements for lithium ion insertion and extraction. The positive electrode active material can be a layered structure material, allowing lithium ions to diffuse in two-dimensional space, or a spinel structure, allowing lithium ions to diffuse in three-dimensional space. Preferably, the positive electrode active material can be selected from one or more of lithium transition metal oxides, or compounds obtained by adding other transition metals, non-transition metals, or non-metals to lithium transition metal oxides. Specifically, the positive electrode active material is preferably selected from one or more of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, and lithium nickel cobalt aluminum oxide.

[0050] In the positive electrode sheet, the positive electrode active material layer may further include a conductive agent and a binder. The type and content of the conductive agent and binder are not specifically limited and can be selected according to actual needs. The binder typically includes fluorinated polyolefin binders. Water is usually a good solvent for the fluorinated polyolefin binder, meaning that the fluorinated polyolefin binder typically has good solubility in water. For example, the fluorinated polyolefin binder may be, but is not limited to, polyvinylidene fluoride (PVDF), PVDF copolymers, or their modified derivatives (e.g., modified with carboxylic acid, acrylic acid, acrylonitrile, etc.). The mass percentage content of the binder in the positive electrode material layer may be limited because the binder itself has poor conductivity, therefore the amount of binder cannot be too high. The conductive agent in the positive electrode sheet can be any conductive agent suitable for secondary batteries in the art, for example, it may be one or more of the following, including but not limited to superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0051] In the positive electrode sheet, the type of positive current collector is not specifically limited and can be selected according to actual needs. The positive current collector is typically a layer, and is usually a structure or component capable of collecting current. The positive current collector can be any material suitable for use as a positive current collector in electrochemical energy storage devices. For example, the positive current collector can be, but is not limited to, metal foil, and more specifically, can be, but is not limited to, nickel foil and aluminum foil.

[0052] Fourthly, this application provides an electrical device, which includes the aforementioned secondary battery.

[0053] The electrical device provided in this application may include the aforementioned battery cells, battery modules, or battery packs. The aforementioned battery cells, battery modules, or battery packs can be used as the power source for the electrical device or as its energy storage unit. The electrical device may be, but is not limited to, mobile devices (e.g., mobile phones, laptops, etc.), electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc. The electrical device can select battery cells, battery modules, or battery packs according to its usage requirements.

[0054] In specific implementations, the electrical device can be a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. To meet the high power and high energy density requirements of the lithium-ion battery for this electrical device, a battery pack or battery module can be used. Another example of an electrical device could be a mobile phone, tablet computer, laptop computer, etc.

[0055] Unless otherwise specified, the various parameters mentioned in this specification have general meanings known in the art and can be measured using methods known in the art. For example, they can be tested according to the methods given in the embodiments of this application. In addition, the optional ranges and options of various parameters given in the various optional embodiments can be combined arbitrarily, and all such combinations are considered to be within the scope of disclosure of this application.

[0056] The embodiments of this application are described in detail below. It should be noted that the embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. In addition, unless otherwise specified, all reagents used in the following embodiments are commercially available or can be synthesized according to the methods described herein or known methods. For reaction conditions not listed, they are also readily available to those skilled in the art.

[0057] The present application will be further described below with reference to embodiments.

[0058] Example 1 1. Preparation of high-temperature expanded graphite powder Artificial graphite was subjected to high-temperature heat treatment at 900℃ for 3 hours in a nitrogen atmosphere to obtain expanded-layer artificial graphite with a graphite interlayer spacing of 0.339nm; the materials were weighed according to the following mass ratio: 80 parts of expanded-layer artificial graphite, 15 parts of natural graphite, 1.2 parts of carbon nanotubes, 1.1 parts of carboxymethyl cellulose powder, 1 part of PPA, 1.2 parts of SBR, and 0.5 parts of nano-alumina with a particle size of 50nm.

[0059] 2. Preparation of negative electrode slurry by stirring The prepared expanded-layer artificial graphite, natural graphite, 30% carboxymethyl cellulose powder, and nano alumina powder were put into a vacuum mixing vessel and dry-mixed for 30 minutes until uniform. Deionized water was added and kneaded for 90 minutes to achieve a solid content of 69%. Then, 70% carboxymethyl cellulose powder, carbon nanotubes, deionized water, and PAA were added and stirred at high speed for 60 minutes. Finally, SBR was added and stirred at low speed for 45 minutes to form a uniform slurry. The final slurry viscosity was stable at 4500 mPa•s.

[0060] 3. Stepped Differential Coating See Figures 3-4 An adjustable stepped coating die head is selected, with a single-layer coating structure. The coating thickness in the middle of the 5μm thick copper foil current collector is 110μm, which decreases linearly towards the two sides. The optimized width of the bare edge of the stepped layer on one side is controlled to 10mm.

[0061] 4. Drying and rolling treatment Three-stage gradient drying: After coating, the electrode is thoroughly dried in sequence through a preheating stage of 125℃-135℃-130℃, a constant-speed drying stage of 130℃-105℃-95℃, and a falling-speed drying stage of 120℃-135℃-110℃; after rolling, the compacted density of the negative electrode is 1.55g / cm³.

[0062] 5. Electrolyte preparation Lithium salt concentration: 1.15 mol / L LiPF6; Composite organic solvent volume ratio: EC 30% + DMC 40% + ethyl propionate 20% + methyl acetate 10%; Composite low-temperature functional additives (percentage of total electrolyte volume): FEC 3 vol%, VEC 1.5 vol%; Electrolyte freezing point: -68℃.

[0063] 6. Cell assembly, electrolyte injection, and formation The cells are assembled using a soft-pack stacking process, with the ceramic layer of the single-sided ceramic diaphragm facing the negative electrode; after liquid injection, they are vacuum sealed and left to stand at a high temperature of 45°C for 48 hours; they are pre-formed at a low temperature of 10°C and charged to 2.6V at 0.01C; then they undergo conventional formation, capacity testing, and constant temperature aging at 50°C for 48 hours to obtain the finished battery cell.

[0064] Example 2 1. Preparation of high-temperature expanded graphite powder Artificial graphite was subjected to high-temperature heat treatment at 900℃ for 3 hours in a nitrogen atmosphere to obtain expanded-layer artificial graphite with a graphite interlayer spacing of 0.339nm; the materials were weighed according to the following mass ratio: 80 parts of expanded-layer artificial graphite, 15 parts of natural graphite, 1.2 parts of carbon nanotubes, 1.1 parts of carboxymethyl cellulose powder, 1 part of PPA, 1.2 parts of SBR, and 0.5 parts of nano-alumina with a particle size of 50nm.

[0065] 2. Preparation of negative electrode slurry by stirring The prepared expanded-layer artificial graphite, natural graphite, 30% carboxymethyl cellulose powder, and nano alumina powder were put into a vacuum mixing vessel and dry-mixed for 30 minutes until uniform. Deionized water was added and kneaded for 90 minutes to achieve a solid content of 69%. Then, 70% carboxymethyl cellulose powder, carbon nanotubes, deionized water, and PAA were added and stirred at high speed for 60 minutes. Finally, SBR was added and stirred at low speed for 45 minutes to form a uniform slurry. The final slurry viscosity was stable at 4500 mPa•s.

[0066] 3. Stepped Differential Coating See Figures 3-4 An adjustable stepped coating die head is selected, with a single-layer coating structure. The coating thickness in the middle of the 5μm thick copper foil current collector is 110μm, which decreases linearly towards the two sides. The optimized width of the bare edge of the stepped layer on one side is controlled to 20mm.

[0067] 4. Drying and rolling treatment Three-stage gradient drying: After coating, the electrode is thoroughly dried in sequence through a preheating stage of 125℃-135℃-130℃, a constant-speed drying stage of 130℃-105℃-95℃, and a falling-speed drying stage of 120℃-135℃-110℃; after rolling, the compacted density of the negative electrode is 1.55g / cm³.

[0068] 5. Electrolyte preparation Lithium salt concentration: 1.15 mol / L LiPF6; Composite organic solvent volume ratio: EC 30% + DMC 40% + ethyl propionate 20% + methyl acetate 10%; Composite low-temperature functional additives (percentage of total electrolyte volume): FEC 3 vol%, VEC 1.5 vol%; Electrolyte freezing point: -68℃.

[0069] 6. Cell assembly, electrolyte injection, and formation The cells are assembled using a soft-pack stacking process, with the ceramic layer of the single-sided ceramic diaphragm facing the negative electrode; after liquid injection, they are vacuum sealed and left to stand at a high temperature of 45°C for 48 hours; they are pre-formed at a low temperature of 10°C and charged to 2.6V at 0.03C; then they undergo conventional formation, capacity testing, and constant temperature aging at 50°C for 48 hours to obtain the finished battery cell.

[0070] Example 3 1. Preparation of high-temperature expanded graphite powder Artificial graphite was subjected to high-temperature heat treatment at 1000℃ in a nitrogen atmosphere for 4 hours to obtain expanded-layer artificial graphite with a graphite interlayer spacing of 0.342nm; the materials were weighed according to the following mass ratio: 80 parts of expanded-layer artificial graphite, 15 parts of natural graphite, 1.2 parts of carbon nanotubes, 1.1 parts of carboxymethyl cellulose powder, 1 part of PPA, 1.2 parts of SBR, and 0.5 parts of nano-alumina with a particle size of 50nm.

[0071] 2. Preparation of negative electrode slurry by stirring The prepared expanded-layer artificial graphite, natural graphite, 30% carboxymethyl cellulose powder, and nano alumina powder were put into a vacuum mixing vessel and dry-mixed for 30 minutes until uniform. Deionized water was added and kneaded for 90 minutes to achieve a solid content of 69%. Then, 70% carboxymethyl cellulose powder, carbon nanotubes, deionized water, and PAA were added and stirred at high speed for 60 minutes. Finally, SBR was added and stirred at low speed for 45 minutes to form a uniform slurry. The final slurry viscosity was stable at 4500 mPa•s.

[0072] 3. Stepped Differential Coating See Figures 3-4 An adjustable stepped coating die head is selected, with a single-layer coating structure. The coating thickness in the middle of the 5μm thick copper foil current collector is 110μm, which decreases linearly towards the two sides. The optimized width of the bare edge of the stepped layer on one side is controlled to 10mm.

[0073] 4. Drying and rolling treatment Three-stage gradient drying: After coating, the electrode is thoroughly dried in sequence through a preheating stage of 125℃-135℃-130℃, a constant-speed drying stage of 130℃-105℃-95℃, and a falling-speed drying stage of 120℃-135℃-110℃; after rolling, the compacted density of the negative electrode is 1.55g / cm³.

[0074] 5. Electrolyte preparation Lithium salt concentration: 1.15 mol / L LiPF6; Composite organic solvent volume ratio: EC 30% + DMC 40% + ethyl propionate 20% + methyl acetate 10%; Composite low-temperature functional additives (percentage of total electrolyte volume): FEC 3 vol%, VEC 1.5 vol%; Electrolyte freezing point: -68℃.

[0075] 6. Cell assembly, electrolyte injection, and formation The cells are assembled using a soft-pack stacking process, with the ceramic layer of the single-sided ceramic diaphragm facing the negative electrode; after liquid injection, they are vacuum sealed and left to stand at a high temperature of 45°C for 48 hours; they are pre-formed at a low temperature of 10°C and charged to 2.6V at 0.03C; then they undergo conventional formation, capacity testing, and constant temperature aging at 50°C for 48 hours to obtain the finished battery cell.

[0076] Example 4 1. Preparation of high-temperature expanded graphite powder Artificial graphite was subjected to high-temperature heat treatment at 900℃ for 3 hours in a nitrogen atmosphere to obtain expanded-layer artificial graphite with a graphite interlayer spacing of 0.339nm; the materials were weighed according to the following mass ratio: 80 parts of expanded-layer artificial graphite, 15 parts of natural graphite, 1.2 parts of carbon nanotubes, 1.1 parts of carboxymethyl cellulose powder, 1 part of PPA, 1.2 parts of SBR, and 0.5 parts of nano-alumina with a particle size of 50nm.

[0077] 2. Preparation of negative electrode slurry by stirring The prepared expanded-layer artificial graphite, natural graphite, 30% carboxymethyl cellulose powder, and nano alumina powder were put into a vacuum mixing vessel and dry-mixed for 30 minutes until uniform. Deionized water was added and kneaded for 90 minutes to achieve a solid content of 69%. Then, 70% carboxymethyl cellulose powder, carbon nanotubes, deionized water, and PAA were added and stirred at high speed for 60 minutes. Finally, SBR was added and stirred at low speed for 45 minutes to form a uniform slurry. The final slurry viscosity was stable at 4500 mPa•s.

[0078] 3. Stepped Differential Coating See Figures 3-4 An adjustable stepped coating die head is selected, with a single-layer coating structure. The coating thickness in the middle of the 5μm thick copper foil current collector is 110μm, which decreases linearly towards the two sides. The optimized width of the bare edge of the stepped layer on one side is controlled to 0.5mm.

[0079] 4. Drying and rolling treatment Three-stage gradient drying: After coating, the electrode is thoroughly dried in sequence through a preheating stage of 125℃-135℃-130℃, a constant-speed drying stage of 130℃-105℃-95℃, and a falling-speed drying stage of 120℃-135℃-110℃; after rolling, the compacted density of the negative electrode is 1.55g / cm³.

[0080] 5. Electrolyte preparation Lithium salt concentration: 1.15 mol / L LiPF6; Composite organic solvent volume ratio: EC 30% + DMC 40% + ethyl propionate 20% + methyl acetate 10%; Composite low-temperature functional additives (percentage of total electrolyte volume): FEC 3 vol%, VEC 1.5 vol%; Electrolyte freezing point: -68℃.

[0081] 6. Cell assembly, electrolyte injection, and formation The cells are assembled using a soft-pack stacking process, with the ceramic layer of the single-sided ceramic diaphragm facing the negative electrode; after liquid injection, they are vacuum sealed and left to stand at a high temperature of 45°C for 48 hours; they are pre-formed at a low temperature of 10°C and charged to 2.6V at 0.02C; then they undergo conventional formation, capacity testing, and constant temperature aging at 50°C for 48 hours to obtain the finished battery cell.

[0082] Example 5 1. Preparation of high-temperature expanded graphite powder Artificial graphite was subjected to high-temperature heat treatment at 900℃ for 3 hours in a nitrogen atmosphere to obtain expanded-layer artificial graphite with a graphite interlayer spacing of 0.339nm; the materials were weighed according to the following mass ratio: 80 parts of expanded-layer artificial graphite, 15 parts of natural graphite, 1.2 parts of carbon nanotubes, 1.1 parts of carboxymethyl cellulose powder, 1 part of PPA, 1.2 parts of SBR, and 0.5 parts of nano-alumina with a particle size of 50nm.

[0083] 2. Preparation of negative electrode slurry by stirring The prepared expanded-layer artificial graphite, natural graphite, 30% carboxymethyl cellulose powder, and nano alumina powder were put into a vacuum mixing vessel and dry-mixed for 30 minutes until uniform. Deionized water was added and kneaded for 90 minutes to achieve a solid content of 69%. Then, 70% carboxymethyl cellulose powder, carbon nanotubes, deionized water, and PAA were added and stirred at high speed for 60 minutes. Finally, SBR was added and stirred at low speed for 45 minutes to form a uniform slurry. The final slurry viscosity was stable at 4500 mPa•s.

[0084] 3. Stepped Differential Coating See Figures 3-4 An adjustable stepped coating die head is selected, with a single-layer coating structure. The coating thickness in the middle of the 5μm thick copper foil current collector is 110μm, which decreases linearly towards the two sides. The optimized width of the bare edge of the stepped layer on one side is controlled to 10mm.

[0085] 4. Drying and rolling treatment Three-stage gradient drying: After coating, the electrode is thoroughly dried in sequence through a preheating stage of 125℃-135℃-130℃, a constant-speed drying stage of 130℃-105℃-95℃, and a falling-speed drying stage of 120℃-135℃-110℃; after rolling, the compacted density of the negative electrode is 1.65g / cm³.

[0086] 5. Electrolyte preparation Lithium salt concentration: 1.15 mol / L LiPF6; Composite organic solvent volume ratio: EC 30% + DMC 40% + ethyl propionate 20% + methyl acetate 10%; Composite low-temperature functional additives (percentage of total electrolyte volume): FEC 3 vol%, VEC 1.5 vol%; Electrolyte freezing point: -68℃.

[0087] 6. Cell assembly, electrolyte injection, and formation The cells are assembled using a soft-pack stacking process, with the ceramic layer of the single-sided ceramic diaphragm facing the negative electrode; after liquid injection, they are vacuum sealed and left to stand at a high temperature of 45°C for 48 hours; they are pre-formed at a low temperature of 10°C and charged to 2.6V at 0.03C; then they undergo conventional formation, capacity testing, and constant temperature aging at 50°C for 48 hours to obtain the finished battery cell.

[0088] Example 6 1. Preparation of high-temperature expanded graphite powder Artificial graphite was subjected to high-temperature heat treatment at 850℃ for 3 hours in a nitrogen atmosphere to obtain expanded-layer artificial graphite with a graphite interlayer spacing of 0.336nm; the materials were weighed according to the following mass ratio: 80 parts of expanded-layer artificial graphite, 15 parts of natural graphite, 1.2 parts of carbon nanotubes, 1.1 parts of carboxymethyl cellulose powder, 1 part of PPA, 1.2 parts of SBR, and 0.5 parts of nano-alumina with a particle size of 50nm.

[0089] 2. Preparation of negative electrode slurry by stirring The prepared expanded-layer artificial graphite, natural graphite, 30% carboxymethyl cellulose powder, and nano alumina powder were put into a vacuum mixing vessel and dry-mixed for 30 minutes until uniform. Deionized water was added and kneaded for 90 minutes to achieve a solid content of 69%. Then, 70% carboxymethyl cellulose powder, carbon nanotubes, deionized water, and PAA were added and stirred at high speed for 60 minutes. Finally, SBR was added and stirred at low speed for 45 minutes to form a uniform slurry. The final slurry viscosity was stable at 4500 mPa•s.

[0090] 3. Stepped Differential Coating See Figures 3-4 An adjustable stepped coating die head is selected, with a single-layer coating structure. The coating thickness in the middle of the 5μm thick copper foil current collector is 110μm, which decreases linearly towards the two sides. The optimized width of the bare edge of the stepped layer on one side is controlled to 10mm.

[0091] 4. Drying and rolling treatment Three-stage gradient drying: After coating, the electrode is thoroughly dried in sequence through a preheating stage of 125℃-135℃-130℃, a constant-speed drying stage of 130℃-105℃-95℃, and a falling-speed drying stage of 120℃-135℃-110℃; after rolling, the compacted density of the negative electrode is 1.55g / cm³.

[0092] 5. Electrolyte preparation Lithium salt concentration: 1.15 mol / L LiPF6; Composite organic solvent volume ratio: EC 30% + DMC 40% + ethyl butyrate 20% + methyl acetate 10%; Composite low-temperature functional additives (percentage of total electrolyte volume): FEC 3 vol%, VEC 1.5 vol%; Electrolyte freezing point: -68℃.

[0093] 6. Cell assembly, electrolyte injection, and formation The cells are assembled using a soft-pack stacking process, with the ceramic layer of the single-sided ceramic diaphragm facing the negative electrode; after liquid injection, they are vacuum sealed and left to stand at a high temperature of 45°C for 48 hours; they are pre-formed at a low temperature of 5°C and charged to 2.6V at 0.01C; then they undergo conventional formation, capacity testing, and constant temperature aging at 50°C for 48 hours to obtain the finished battery cell.

[0094] Example 7 1. Preparation of high-temperature expanded graphite powder Artificial graphite was subjected to high-temperature heat treatment at 900℃ for 3 hours in a nitrogen atmosphere to obtain expanded-layer artificial graphite with a graphite interlayer spacing of 0.339nm; the materials were weighed according to the following mass ratio: 80 parts of expanded-layer artificial graphite, 15 parts of natural graphite, 1.2 parts of carbon nanotubes, 1.1 parts of carboxymethyl cellulose powder, 1 part of PPA, 1.2 parts of SBR, and 0.5 parts of nano-alumina with a particle size of 50nm.

[0095] 2. Preparation of negative electrode slurry by stirring The prepared expanded-layer artificial graphite, natural graphite, 30% carboxymethyl cellulose powder, and nano alumina powder were put into a vacuum mixing vessel and dry-mixed for 30 minutes until uniform. Deionized water was added and kneaded for 90 minutes to achieve a solid content of 69%. Then, 70% carboxymethyl cellulose powder, carbon nanotubes, deionized water, and PAA were added and stirred at high speed for 60 minutes. Finally, SBR was added and stirred at low speed for 45 minutes to form a uniform slurry. The final slurry viscosity was stable at 4500 mPa•s.

[0096] 3. Stepped Differential Coating See Figures 3-4 An adjustable stepped coating die head is selected, with a single-layer coating structure. The coating thickness in the middle of the 5μm thick copper foil current collector is 110μm, which decreases linearly towards the two sides. The optimized width of the bare edge of the stepped layer on one side is controlled to 10mm.

[0097] 4. Drying and rolling treatment Three-stage gradient drying: After coating, the electrode is thoroughly dried in sequence through a preheating stage of 125℃-135℃-130℃, a constant-speed drying stage of 130℃-105℃-95℃, and a falling-speed drying stage of 120℃-135℃-110℃; after rolling, the compacted density of the negative electrode is 1.45g / cm³.

[0098] 5. Electrolyte preparation Lithium salt concentration: 1.15 mol / L LiPF6; Composite organic solvent volume ratio: EC 30% + DMC 40% + ethyl propionate 20% + methyl acetate 10%; Composite low-temperature functional additives (percentage of total electrolyte volume): FEC 3 vol%, VEC 1.5 vol%; Electrolyte freezing point: -68℃.

[0099] 6. Cell assembly, electrolyte injection, and formation The cells are assembled using a soft-pack stacking process, with the ceramic layer of the single-sided ceramic diaphragm facing the negative electrode; after liquid injection, they are vacuum sealed and left to stand at a high temperature of 45°C for 48 hours; they are pre-formed at a low temperature of 10°C and charged to 2.8V at 0.03C; then they undergo conventional formation, capacity testing, and constant temperature aging at 50°C for 48 hours to obtain the finished battery cell.

[0100] Example 8 1. Preparation of high-temperature expanded graphite powder Artificial graphite was subjected to high-temperature heat treatment at 900℃ for 3 hours in a nitrogen atmosphere to obtain expanded-layer artificial graphite with a graphite interlayer spacing of 0.339nm; the materials were weighed according to the following mass ratio: 80 parts of expanded-layer artificial graphite, 15 parts of natural graphite, 1.2 parts of carbon nanotubes, 1.1 parts of carboxymethyl cellulose powder, 1 part of PPA, 1.2 parts of SBR, and 0.5 parts of nano-alumina with a particle size of 50nm.

[0101] 2. Preparation of negative electrode slurry by stirring The prepared expanded-layer artificial graphite, natural graphite, 30% carboxymethyl cellulose powder, and nano alumina powder were put into a vacuum mixing vessel and dry-mixed for 30 minutes until uniform. Deionized water was added and kneaded for 90 minutes to achieve a solid content of 69%. Then, 70% carboxymethyl cellulose powder, carbon nanotubes, deionized water, and PAA were added and stirred at high speed for 60 minutes. Finally, SBR was added and stirred at low speed for 45 minutes to form a uniform slurry. The final slurry viscosity was stable at 4500 mPa•s.

[0102] 3. Stepped Differential Coating See Figures 3-4 An adjustable stepped coating die head is selected, with a single-layer coating structure. The coating thickness in the middle of the 5μm thick copper foil current collector is 110μm, which decreases linearly towards the two sides. The optimized width of the bare edge of the stepped layer on one side is controlled to 10mm.

[0103] 4. Drying and rolling treatment Three-stage gradient drying: After coating, the electrode is thoroughly dried in sequence through a preheating stage of 125℃-135℃-130℃, a constant-speed drying stage of 130℃-105℃-95℃, and a falling-speed drying stage of 120℃-135℃-110℃; after rolling, the compacted density of the negative electrode is 1.55g / cm³.

[0104] 5. Electrolyte preparation Lithium salt concentration: 1.15 mol / L LiPF6; Composite organic solvent volume ratio: EC 30% + DMC 40% + ethyl acetate 20% + methyl propionate 10%; Composite low-temperature functional additives (percentage of total electrolyte volume): FEC 3 vol%, VEC 1.5 vol%; Electrolyte freezing point: -65℃.

[0105] 6. Cell assembly, electrolyte injection, and formation The cells are assembled using a soft-pack stacking process, with the ceramic layer of the single-sided ceramic diaphragm facing the negative electrode; after liquid injection, they are vacuum sealed and left to stand at a high temperature of 45°C for 48 hours; they are pre-formed at a low temperature of 10°C and charged to 2.6V at 0.03C; then they undergo conventional formation, capacity testing, and constant temperature aging at 50°C for 48 hours to obtain the finished battery cell.

[0106] Comparative Example 1 1. Preparation of graphite powder The graphite was not subjected to high-temperature layer expansion treatment, and the graphite interlayer spacing was 0.335nm. The materials were weighed according to the following mass ratio: 80 parts of conventional artificial graphite, 1.2 parts of carbon nanotubes, 1.1 parts of carboxymethyl cellulose powder, 1 part of PPA, and 1.2 parts of SBR.

[0107] 2. Preparation of negative electrode slurry by stirring Take conventional artificial graphite and 30% carboxymethyl cellulose powder, put them into a vacuum mixing vessel and dry mix for 30 minutes until uniform. Add deionized water and knead for 90 minutes to achieve a solid content of 69%. Then add 70% carboxymethyl cellulose powder, carbon nanotubes, deionized water, and PAA, and stir at high speed for 60 minutes. Then add SBR and stir at low speed for 45 minutes to form a uniform slurry. The final slurry viscosity is stable at 4000 mPa•s.

[0108] 3. Conventional coating The surface of the negative electrode current collector is coated with a uniform thickness of 110μm across the entire surface, with an optimized edge region without steps. 4. Drying and rolling treatment Three-stage gradient drying: After coating, the electrode is thoroughly dried in sequence through a preheating stage of 125℃-135℃-130℃, a constant speed drying stage of 130℃-105℃-95℃, and a falling speed drying stage of 120℃-135℃-110℃; after rolling, the compacted density of the negative electrode is 1.55g / cm³.

[0109] 5. Electrolyte preparation Lithium salt concentration: 1.15 mol / L LiPF6; Composite organic solvent volume ratio: EC 60% + DMC 40%; Composite low-temperature functional additives (percentage of total electrolyte volume): FEC 3 vol%, VEC 1.5 vol%; Electrolyte freezing point: -45℃.

[0110] 6. Cell assembly, electrolyte injection, and formation The cells are assembled using a soft-pack stacking process, with the ceramic layer of the single-sided ceramic diaphragm facing the negative electrode; after liquid injection, they are vacuum sealed and left to stand at 45°C for 48 hours; conventional formation, capacity testing, and constant temperature aging at 50°C for 48 hours are then performed to obtain the finished battery cell.

[0111] Comparative Example 2 1. Preparation of graphite powder The graphite was not subjected to high-temperature layer expansion treatment, and the graphite interlayer spacing was 0.335nm. The materials were weighed according to the following mass ratio: 80 parts of conventional artificial graphite, 1.2 parts of carbon nanotubes, 1.1 parts of carboxymethyl cellulose powder, 1 part of PPA, and 1.2 parts of SBR.

[0112] 2. Preparation of negative electrode slurry by stirring Take conventional artificial graphite and 30% carboxymethyl cellulose powder, put them into a vacuum mixing vessel and dry mix for 30 minutes until uniform. Add deionized water and knead for 90 minutes to achieve a solid content of 69%. Then add 70% carboxymethyl cellulose powder, carbon nanotubes, deionized water, and PAA, and stir at high speed for 60 minutes. Then add SBR and stir at low speed for 45 minutes to form a uniform slurry. The final slurry viscosity is stable at 4000 mPa•s.

[0113] 3. Conventional coating The surface of the negative electrode current collector is coated with a uniform thickness of 110μm across the entire surface, with an optimized edge region without steps. 4. Drying and rolling treatment Three-stage gradient drying: After coating, the electrode is thoroughly dried in sequence through a preheating stage of 125℃-135℃-130℃, a constant-speed drying stage of 130℃-105℃-95℃, and a falling-speed drying stage of 120℃-135℃-110℃; after rolling, the compacted density of the negative electrode is 1.55g / cm³.

[0114] 5. Electrolyte preparation Lithium salt concentration: 1.15 mol / L LiPF6; Composite organic solvent volume ratio: EC 30% + DMC 40% + ethyl propionate 20% + methyl acetate 10%; Composite low-temperature functional additives (percentage of total electrolyte volume): FEC 3 vol%, VEC 1.5 vol%; Electrolyte freezing point: -68℃.

[0115] 6. Cell assembly, electrolyte injection, and formation The cells are assembled using a soft-pack stacking process, with the ceramic layer of the single-sided ceramic diaphragm facing the negative electrode; after liquid injection, they are vacuum sealed and left to stand at a high temperature of 45°C for 48 hours; they are pre-formed at a low temperature of 10°C and charged to 2.6V at 0.03C; then they undergo conventional formation, capacity testing, and constant temperature aging at 50°C for 48 hours to obtain the finished battery cell.

[0116] Comparative Example 3 1. Preparation of graphite powder The graphite was not subjected to high-temperature layer expansion treatment, and the graphite interlayer spacing was 0.335nm. The materials were weighed according to the following mass ratio: 80 parts of conventional artificial graphite, 1.2 parts of carbon nanotubes, 1.1 parts of carboxymethyl cellulose powder, 1 part of PPA, and 1.2 parts of SBR.

[0117] 2. Preparation of negative electrode slurry by stirring Take conventional artificial graphite and 30% carboxymethyl cellulose powder, put them into a vacuum mixing vessel and dry mix for 30 minutes until uniform. Add deionized water and knead for 90 minutes to achieve a solid content of 69%. Then add 70% carboxymethyl cellulose powder, carbon nanotubes, deionized water, and PAA, and stir at high speed for 60 minutes. Then add SBR and stir at low speed for 45 minutes to form a uniform slurry. The final slurry viscosity is stable at 4000 mPa•s.

[0118] 3. Stepped Differential Coating See Figures 3-4 An adjustable stepped coating die head is selected, with a single-layer coating structure. The coating thickness in the middle of the 5μm thick copper foil current collector is 110μm, which decreases linearly towards the two sides. The optimized width of the bare edge of the stepped layer on one side is controlled to 10mm.

[0119] 4. Drying and rolling treatment Three-stage gradient drying: After coating, the electrode is thoroughly dried in sequence through a preheating stage of 125℃-135℃-130℃, a constant-speed drying stage of 130℃-105℃-95℃, and a falling-speed drying stage of 120℃-135℃-110℃; after rolling, the compacted density of the negative electrode is 1.55g / cm³.

[0120] 5. Electrolyte preparation Lithium salt concentration: 1.15 mol / L LiPF6; Composite organic solvent volume ratio: EC 60% + DMC 40%; Composite low-temperature functional additives (percentage of total electrolyte volume): FEC 3 vol%, VEC 1.5 vol%; Electrolyte freezing point: -45℃.

[0121] 6. Cell assembly, electrolyte injection, and formation The cells are assembled using a soft-pack stacking process, with the ceramic layer of the single-sided ceramic diaphragm facing the negative electrode; after liquid injection, they are vacuum sealed and left to stand at 45°C for 48 hours; conventional formation, capacity testing, and constant temperature aging at 50°C for 48 hours are then performed to obtain the finished battery cell.

[0122] Comparative Example 4 1. Preparation of graphite powder The graphite was not subjected to high-temperature layer expansion treatment, and the graphite interlayer spacing was 0.335nm. The materials were weighed according to the following mass ratio: 80 parts of conventional artificial graphite, 15 parts of natural graphite, 1.2 parts of carbon nanotubes, 1.1 parts of carboxymethyl cellulose powder, 1 part of PPA, and 1.2 parts of SBR.

[0123] 2. Preparation of negative electrode slurry by stirring Conventional artificial graphite, natural graphite, and 30% carboxymethyl cellulose powder were added to a vacuum mixing vessel and dry-mixed for 30 minutes until homogeneous. Deionized water was added and kneaded for 90 minutes to achieve a solid content of 69%. Then, 70% carboxymethyl cellulose powder, carbon nanotubes, deionized water, and PAA were added and stirred at high speed for 60 minutes. Finally, SBR was added and stirred at low speed for 45 minutes to form a uniform slurry. The final slurry viscosity was stable at 4500 mPa•s.

[0124] 3. Stepped Differential Coating See Figures 3-4 An adjustable stepped coating die head is selected, with a single-layer coating structure. The coating thickness in the middle of the 5μm thick copper foil current collector is 110μm, which decreases linearly towards the two sides. The optimized width of the bare edge of the stepped layer on one side is controlled to 10mm.

[0125] 4. Drying and rolling treatment Three-stage gradient drying: After coating, the electrode is thoroughly dried in sequence through a preheating stage of 125℃-135℃-130℃, a constant-speed drying stage of 130℃-105℃-95℃, and a falling-speed drying stage of 120℃-135℃-110℃; after rolling, the compacted density of the negative electrode is 1.55g / cm³.

[0126] 5. Electrolyte preparation Lithium salt concentration: 1.15 mol / L LiPF6; Composite organic solvent volume ratio: EC 30% + DMC 40% + ethyl acetate 20% + methyl propionate 10%; Composite low-temperature functional additives (percentage of total electrolyte volume): FEC 3 vol%, VEC 1.5 vol%; Electrolyte freezing point: -65℃.

[0127] 6. Cell assembly, electrolyte injection, and formation The cells are assembled using a soft-pack stacking process, with the ceramic layer of the single-sided ceramic diaphragm facing the negative electrode; after liquid injection, they are vacuum sealed and left to stand at a high temperature of 45°C for 48 hours; they are pre-formed at a low temperature of 10°C and charged to 2.6V at 0.03C; then they undergo conventional formation, capacity testing, and constant temperature aging at 50°C for 48 hours to obtain the finished battery cell.

[0128] Performance testing 1. Room temperature cycling test: 25℃ environment, 1C constant current charge and discharge, voltage window 2.5-3.7V, 1000 cycles; 2. Low-temperature discharge test: -20℃ constant temperature chamber for 4 hours, 0.5C constant current discharge; 3. Lithium plating observation: After disassembling the battery cell after 1000 cycles, the side morphology of the negative electrode was observed using an optical microscope; 4. Safety test: The fully charged battery cell is punctured with a 1mm steel needle and overcharged to 5.0V with a constant current of 1C. Observe whether it smokes or catches fire.

[0129] Test Results 1. Lithium plating at the edge Examples 1-8: The negative electrode sheet has a smooth side surface with no white lithium powder deposits and no dendrites; Comparative Examples 1, 2, and 3: The edges of the negative electrode are largely white, with lithium powder visible to the naked eye and dendrites observed under a microscope.

[0130] 2. Capacity retention rate after 1000 room temperature cycles Table 1

[0131] 3. Capacity retention rate at -20℃ and 0.5C Table 2

[0132] 4. Safety performance Examples 1-8: Acupuncture and overcharging only caused a slight temperature rise, with a maximum temperature of only 72°C. There was no smoke, no fire, no explosion, and no thermal runaway. Comparative Example 1: Localized continuous heat was observed after acupuncture, with a maximum temperature of 105℃, and the diaphragm was significantly damaged.

[0133] The experimental results above show that the solution provided in this application has the following advantages: Lithium plating suppression effect: The stepped bare edge structure continuously replenishes the edge electrolyte. After 1000 deep cycles, there is no white lithium plating powder or dendrite formation on the negative electrode side. Compared with traditional equal-thickness coated cells, it completely eliminates the edge lithium plating failure mode, significantly improves the cell safety level, and there is no smoke, fire or thermal runaway phenomenon during needle penetration and 1C overcharge.

[0134] Room temperature cycle life: Negative electrode modification + stable SEI film reduces active lithium loss, 93% capacity retention rate after 1000 1C room temperature cycles, compared with traditional cells (Comparative Example 1) 80% capacity retention rate after 1000 1C room temperature cycles, an improvement of 13 percentage points, and overall cycle life is improved by more than 15%, significantly reducing the replacement cycle of energy storage and power batteries.

[0135] Low-temperature discharge performance: With widened graphite interlayer spacing and low freezing point electrolyte, the discharge capacity retention rate is 88% at -20℃ and 0.5C, compared to only 65% ​​for traditional cells. This significantly improves the problem of vehicle range reduction in northern winters and can support stable fast charging in low-temperature environments without the risk of lithium plating during charging.

[0136] Mass production adaptation advantages: Only the coating die head needs to be replaced and the slurry formula and formation temperature zone need to be adjusted. Existing mixing, coating, rolling and formation equipment does not need to be replaced. The raw materials are all common materials in the lithium battery industry. There are no scarce high-cost auxiliary materials. The increase in manufacturing cost per cell is less than 1%, which is suitable for large-scale production.

[0137] Versatility: This technology can be used for square aluminum shells, pouch stacked cells, and cylindrical wound cells. It is also compatible with ternary cathode and lithium iron phosphate cathode systems. It can be applied to passenger vehicle power batteries, industrial and commercial energy storage, and low-temperature special power supplies, with a wide range of applications.

[0138] As can be seen from the above, this application provides a negative electrode sheet, a secondary battery, a method for preparing the secondary battery, and an electrical device for use. It eliminates edge thickness defects from the source of cell coating, optimizes low-temperature lithium-ion dynamics through material modification, and stabilizes the negative electrode SEI film with a special electrolyte and formation process, thus completely solving the bottleneck of existing lithium-ion battery coupling technology. All raw materials and processing equipment are mature mass-produced supporting equipment in the lithium battery industry. The process improvement and control are simple, and the production cost is controllable. It can be quickly adapted to the mass production of power batteries and energy storage batteries, and has significant technological competitive advantages and commercial promotion value in the new energy vehicle and new energy storage sectors.

[0139] The above are merely preferred embodiments of this application and are not intended to limit this application. Various modifications and variations can be made to this application by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this application should be included within the protection scope of this application.

Claims

1. A negative electrode sheet, characterized in that, include: Negative electrode current collector; And an active material layer disposed on at least one surface of the negative electrode current collector; The active material layer includes a central region and edge regions located on both sides of the central region along the width direction; The thickness of the middle region is uniform, and the thickness of the edge region decreases continuously from the middle region to the two sides of the negative electrode current collector, with a thickness range H of 3μm-35μm. The active material layer includes a negative electrode active material, a conductive agent, a binder, and a ceramic filler, and the negative electrode active material includes graphite; The graphite includes expanded-layer artificial graphite and natural graphite, wherein: the expanded-layer artificial graphite has a mass percentage content of 50%-90% in the active material layer, and the natural graphite has a mass percentage content of 5%-20% in the active material layer; wherein: the expanded-layer artificial graphite is obtained by expanding and modifying artificial graphite under an inert atmosphere at 800℃-1200℃, and the graphite crystal interlayer spacing of the expanded-layer artificial graphite is 0.336nm-0.342nm.

2. The negative electrode sheet according to claim 1, characterized in that, The width of the middle region is 30mm-800mm, and the edge regions on both sides of the middle region are symmetrically arranged, with the width W of the edge region on one side being 0.5mm-20.0mm.

3. The negative electrode sheet according to claim 1, characterized in that, The thickness of the intermediate region is 100μm-120μm.

4. The negative electrode sheet according to claim 1, characterized in that, The surface of the negative electrode current collector is provided with at least one layer of the active material. When the active material layer has two or more layers, the type and particle size of the graphite in the different active material layers are different.

5. The negative electrode sheet according to claim 1, characterized in that, The binder includes at least one of sodium carboxymethyl cellulose, polyacrylic acid, polyvinyl alcohol, polyamide-imide, polyacrylate, polyacrylate, polyimide, and nitrile rubber; the conductive agent includes at least one of carbon nanotubes, conductive carbon black, discrete carbon nanotubes, conductive graphite, and graphene; and the ceramic filler includes at least one of nano-alumina, boehmite, and zirconium oxide.

6. The negative electrode sheet according to any one of claims 1-5, characterized in that, The active material layer, by mass percentage, comprises: 50%-90% expanded artificial graphite, 5%-20% natural graphite, 0.3%-2% carbon nanotubes, 0.6%-1.5% carboxymethyl cellulose, 0.5%-1.5% polyacrylic acid, 0.8%-2% styrene-butadiene rubber latex, and 0.5%-1.2% nano-alumina; the nano-alumina has a particle size of 20nm-90nm.

7. A secondary battery, said secondary battery comprising a positive electrode, a negative electrode, a separator, an electrolyte, and a packaging shell, characterized in that, The negative electrode sheet is the negative electrode sheet according to any one of claims 1-6.

8. The secondary battery according to claim 7, characterized in that, The electrolyte comprises a solute, a composite organic solvent, and a composite low-temperature functional additive, wherein: The solute in the electrolyte includes at least one of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, LiDFOB, and LiBOB, and the concentration of the solute in the electrolyte is 1.0 mol / L to 1.3 mol / L. The composite organic solvent includes ethylene carbonate, dimethyl carbonate, and low-viscosity low-temperature ester solvents. The low-viscosity low-temperature ester solvents include at least one of ethyl propionate, methyl acetate, ethyl acetate, methyl propionate, methyl butyrate, and propyl acetate. The overall freezing point of the composite organic solvent is ≤-65℃. The composite low-temperature functional additive includes 2%-3% fluoroethylene carbonate and 0.5%-2% ethylene sulfate, which constitute 2%-3% of the total volume of the electrolyte.

9. The secondary battery according to claim 7, characterized in that, The separator comprises one or more of polyethylene and polypropylene coated with single-sided nano-ceramic coating, and the ceramic coating surface of the separator is arranged facing the negative electrode sheet.

10. A method for preparing a secondary battery according to any one of claims 7-8, characterized in that, The process includes the following steps: coating the active material layer onto the negative electrode current collector, followed by drying and rolling, assembly, liquid injection, formation, and capacity testing to obtain the secondary battery.

11. The preparation method according to claim 10, characterized in that, The method of coating the active material layer on the negative electrode current collector includes: using a segmented adjustable stepped coating die to coat the active material layer on the negative electrode current collector, with a coating thickness of 100μm-120μm in the middle region, and the coating thickness decreasing linearly from the middle region to the edge regions on both sides, with the thickness difference controlled between 3μm-35μm.

12. The preparation method according to claim 10, characterized in that, The drying and rolling process includes: after coating the active material layer onto the negative electrode current collector, thoroughly drying it in a preheating section of 125℃-135℃-130℃, a constant-speed drying section of 130℃-105℃-95℃, and a decreasing-speed drying section of 120℃-135℃-110℃; after drying, rolling the negative electrode sheet to control the compaction density at 1.45g / cm³-1.65g / cm³.

13. The preparation method according to claim 10, characterized in that, Assembly and electrolyte injection include: assembling and packaging the positive electrode, the separator, and the negative electrode using a winding or stacking process according to product requirements; injecting a quantitative amount of electrolyte into the cell and then vacuum sealing it; and allowing it to stand at room temperature for 36-48 hours to allow the electrolyte to fully wet the electrode.

14. The preparation method according to claim 10, characterized in that, Formation and capacity testing include low-temperature pre-formation, conventional formation, and capacity testing aging. Low-temperature pre-formation includes controlling the ambient temperature at 5℃-10℃ and using a step-by-step constant current charging method with an extremely small current of 0.01C-0.03C to the cutoff voltage of 3.2V.

15. The preparation method according to claim 10, characterized in that, The method for preparing the secondary battery is applicable to lithium-ion batteries in nickel-cobalt-manganese, lithium manganese oxide, lithium iron phosphate, and lithium manganese iron phosphate systems.

16. An electrical appliance, characterized in that, The electrical device includes the secondary battery as described in any one of claims 7-8 and / or the secondary battery prepared by the preparation method as described in any one of claims 10-15.